(untitled) (Docentes 2.0 Journal, 2020)
Learning and communication technologies (TAC) orient information and communication technologies (ICT) towards formative uses; reorienting the teaching - learning - evaluation process towards the learning subject (focused on the student), using a set of services, networks, applications and devices offered by the digital era aimed at improving the quality of learning processes. This study focuses on knowing how the use of technology allows to narrow the gaps in social inequalities by bringing knowledge and information closer to those who, due to social, economic and gender issues, have not completed their academic training at a higher level, under this context. The teacher professionalization of those who exercise the functions of teachers in the Province of Morona Santiago, both in the Hispanic and bilingual jurisdiction, have benefited from the distance courses offered by the National University of Education of Ecuador (UNAE), based on a pedagogical model Through the application of learning and communication technologies (TAC), it also promotes lifelong learning. Teachers interact with teachers through the Virtual Teaching and Learning Environment (EVEA), this platform is friendly and easy to use for those who fulfill the functions of teachers or students in this career. The result is centered on the experience obtained by relating the practice in face-to-face and virtual environments, as in the reflection of the importance of technology to erase borders of all kinds with the sole objective of generating new alternatives that help to educational excellence. The interaction between the TACs of the participating student-teachers generates motivation to move towards the professional development of teachers.